SERVQUAL as a Socio-Technical Approach to Measuring e-Government Service Quality and Guiding e-Governance Strategies - Twinomurinzi, Hossana; Zwane, Mphikeleli Gabriel; Debusho, Legesse Kassa (LINK Centre, University of the Witwatersrand (Wits), Johannesburg, 2012)
e-Government services and e-governance have been embraced in many African countries. Nonetheless, measuring the value of e-government remains a challenge. Key to a successful evaluation of progress towards e-governance is the contextual approach, in which ICT is embedded as part of a holistic solution to governance. When carried through without considering the complementary influences of society on ICT and of ICT on society, e-government services can lead to little added value, or even to an exacerbation of societal problems and lack of progress towards e-governance. Although much has been written on e-governance in Africa, few authors have extended the discussion to measuring quality of service and lack of progress towards e-governance. In South Africa, the Batho Pele (People First) policy of service quality is the contextual approach within which e-governance is embedded, because of its good governance attributes. This article relates Batho Pele to SERVQUAL, a framework widely used to measure customer service quality in the retail sector, and adapts the framework for measuring service quality in community e-government service centres, known as Thusong Service Centres (TSC). The analysis, using Structural Equation Modeling (SEM), is consistent with what is known: service quality in TSCs is low and requires regular measurement and evaluation to inform future quality improvements. The article argues that an adapted SERVQUAL instrument, taking into account Batho Pele principles and situational context, can be used as a guide to innovation in e-government service delivery. It is an appropriate sociotechnical tool to collect data to inform e-governance strategies in African countries which share the same social context as South Africa.
Keywords: e-government service quality, e-governance strategies, measurement, socio-technical approach